The Slowdown in Global Trade : A Symptom of A Weak Recovery - Aslam, Aqib.; Boz, Emine; Cerutti, Eugenio; Poplawski Ribeiro, Marcos (Washington, D.C. : International Monetary Fund, 2017)
Global trade growth has slowed since 2012 relative both to its strong historical performance and to overall economic growth. This paper aims to quantify the role of weak economic growth and changes in its decomposition in accounting for the slowdown in trade using a reduced form and a structural approach. Both analytical investigations suggest that the overall weakness in economic activity, particularly investment, has been the primary restraint on trade growth, accounting for over 80 percent of the decline in the growth of the volume of goods trade between 2012-16 and 2003-07. However, other factors are also weighing on trade in recent years, especially in emerging market and developing economies, as evidenced by the non-negligible role attributed to trade costs by the structural approach.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet